IMPLEMENTATION OF THE PAIN PROTOCOL IN A TERTIARY HOSPITAL IN THE SERTÃO OF CEARÁ - Tavares, Patrícia de Lemos Negreiros; Fonseca de Queiroz, Rafael; Miranda Macedo, Leonardo; Rodrigues da Silva, Francisco Daniel; Nobre dos Santos, Odilia Cynara; Fernandes de Araujo, José Décio (Cadernos ESP, 2024)
This report aims to describe the experience of the pain protocol implemented in a tertiary hospital in Ceará. This is an experience report, which addresses the process of implementation and management of the pain approach and control protocol, carried out by management and assistance professionals at the local hospital in the report, between the years 2022 and 2023. 90% compliance was obtained in the effectiveness rate of protocol measures and 86.2% in the compliance rate for pain reassessment, highlighting adherence rate above 85% in the Hospital units. From this perspective, we consider promising results from the protocol, with a positive impact on the patient experience and better care provided.